The Role of Fintech, Real-Time Data Analytics, and ERP Systems in Strengthening Budget Accuracy and Strategic Decision-Making in Indonesian Corporate Accounting - Utami, Mega; Barus, Irwan Irawadi; Arum, Mega; Mahdi, Fadilla Muhammad; Sugihyanto, Toto (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The increasing complexity of corporate operations and the growing demand for timely, data-driven decisions have encouraged organizations to integrate digital technologies into their accounting systems to improve budgeting processes and support strategic decision-making. This study examines the role of fintech adoption, real-time data analytics capability, and Enterprise Resource Planning (ERP) system integration in enhancing budget accuracy and strategic decision-making in Indonesian corporate accounting. A quantitative research design was employed, and data were collected from 150 accounting and finance professionals in Indonesian corporations using a structured questionnaire measured on a five-point Likert scale. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to examine the relationships among the research variables. The results indicate that fintech adoption, real-time data analytics capability, and ERP system integration have significant positive effects on budget accuracy, indicating that organizations adopting digital accounting technologies are able to produce more accurate, timely, and reliable budgeting information. Furthermore, budget accuracy has a strong positive influence on strategic decision-making, enabling management to make more effective, informed, and forward-looking decisions. The findings also reveal that budget accuracy mediates the relationship between digital accounting technologies and strategic decision-making, suggesting that the strategic impact of digital transformation is largely achieved through improvements in budgeting quality. This study contributes empirical evidence from an emerging economy context and provides practical insights for managers seeking to strengthen budgeting accuracy and strategic decision-making through digital accounting implementation. These results highlight the importance of aligning accounting technology investments with organizational strategy and managerial capabilities development.